THE INVESTIGATION OF THE RELATIONSHIP BETWEEN TEACHER CANDIDATES’ TEACHER SELF-EFFICACY BELIEFS AND COMMUNICATION SKILLS - Soner ARIK (International Journal of Eurasia Social Sciences, 2018)
Teaching profession is regarded as a centuries old profession to continue in the future as well. In literature, it is frequently stated that teachers’ beliefs on their occupational self-efficacy is of great significance and it will be determinant in performing the profession. Communication is considered the most important dimension of teaching profession and effective communication is of particular importance. In this study, teacher candidates’ occupational self-efficacy beliefs, their communication skills and the relation between these two are investigated. The sampling of the study consist of teacher candidates studying at the faculty of education at a state university in 2017-2018 academic years. The data was obtained on voluntary basis through ‘Teacher Self-Efficacy Beliefs Scale’ by Çolak, Yorulmaz and Altınkurt (2017), ‘Communication Skills Scale’ by Korkut-Owen and Bugay (2014) and a Personal Profile Form prepared by the researcher. According to the findings of the study, while no significant difference was observed in the teacher self-efficacy beliefs and communication skills of the participants in terms of gender, significant differences were found in terms in terms of the variables class level, department and membership of a university club. Also, a positive medium-level significant relation was found between the teacher self-efficacy beliefs and communication skills of the teacher candidates. The findings of the study were discussed within the related literature and various suggestions were made accordingly.